The Problem of Being in the Middle Ages: An Essay on Medieval History of Being - CHERMAN, Florin (Studia Universitatis Babeș-Bolyai Philosophia, 2024)
The main question of this paper is whether, and if yes – how, is it possible to speak about the history of being in the Midde Ages? Heidegger’s writings suggest that indeed it is possible, and said history can be outlined with the help of the concept of production. However, one cannot escape the rightful feeling that there is more to this epoch of being than it is suggested. There is a doubt whether Heidegger himself went far enough in deconstructing the Medieval epoch of being. Thus, the second part of the paper presents an endeavor of describing the problem of being in the Middle Ages, using Jan A. Aertsen’s distinctions and insights.